Gestion Thermo-Hygrometrique Des Structures De Stockage Du Mais En Zone Equatoriale Humide. (Journal of Science and Technology, 2016)
In the humid and hot zones like Togo, where post harvesting losses are considerable, the author shows that it is possible to preserve maize for a very long period by using two modes of storage:Storing the maize (in spathe) in improved traditional granary which is subjected to intermittent regime of ‘smoking’ for at least 155 days.Storing the grains of the maize in silos under controlled atmospheric conditions and subjecting it to alternate cycles of 12 to 15 days of continuous hot air ventilation and 65 to 70 days without hot air ventilation.The stability of iodine index recorded indicates that the principal nutritional values of grain have been preserved during the period of storage. The experimental results and those deduced from the theorical model of energy and humidity transfer in the heap of maize are presented and discussed.